A REVISIT TO RETURN SEASONALITY AND THE TAX SELLING HYPOTHESIS IN THE KOREAN STOCK MARKET - Chang-Mo Bae (Global Business and Finance Review, 1996)
This study empirically examines the January seasonality and also investigates the validity ofthe tax selling hypothesis in the Korean Stock Market. Since there is no tax on capital gains for individual investors and no tax benefit for losses on securities in Korea, this study offers a unique opportunity for testing this hypothesis. Our statistical results indicate that there is no January seasonality in the Korean Stock Market. The highest return does not occur in the month ofJanuary, but in March. The absence ofany capital gains tax on securities in Korea may be one possible explanation for the absence of a January effect on the Korean Stock Market. Howeve1; conclusive evidence o f this requires a great deal more research.